Contribution of Education to Economic Development - Alali, W Y (University of Oxford, 2022)
Abstract: The concept of education is an umbrella term for academic studies and learning to develop talents and skills; it's a pluralistic comprehensive term. The first paper's objective is a theoretical view. Education is one of the essential factors in economic development, which means human capital investment is the fundamental issue for the countries to sustainable economic development achievement; furthermore, it sang the community members to grasp themselves and the surrounding circumstances and the impact of the global variants. Education improves the quality of living; and benefits society; in addition, it increases productivity and innovation; subsequently promoting entrepreneurship; therefore, it is a crucial factor in the economic development of countries and improves income equality of the societies. Education helps the poor and improves their food intake by increasing families' incomes and spending on health and food, in order to raise their standard of living and make them have better healthier choices.